Pengamanan Objek Vital, Pengamanan File, Pengamanan Cyber Terhadap Pt. Kereta Api Indonesia - Edy Soesanto; Aureta Zhabila Eka Putri; Bella Nugraheni; Cut Zia Auralia; Dina Juniarti Barokah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In the increasingly advanced digital era, information security is a top priority for companies to protect their important data from unwanted threats. PT Kereta Api as a company engaged in the field of rail transportation has many vital object files, including customer data, financial information, and business plans which must be kept confidential. The importance of securing vital object files and identifying various security risks that may occur in PT Kereta Api. Then, an analysis of the methods and technologies that can be used to protect these vital object files will be carried out. Several aspects that will be analyzed include data encryption, access control, intrusion detection, and user activity monitoring. This paper uses a security analysis approach which consists of identifying threats, evaluating risks, and selecting appropriate security controls. The results of the analysis will provide a better understanding of the state of security of vital object files at PT Kereta Api and provide recommendations for improving the existing security system.